Selected Economic Theories and Their Relevance to Higher Education Funding - Grabińska, Barbara (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The objective of the article is to present the main economic theories as they apply to higher education financing: human capital theory, enterprise (organisation) theory and the economics of the public sector. Human capital theory is applied in the study of the impact of monetary and non-monetary determinants on decisions concerning entrance into higher education. The theory of the enterprise leads to a better understanding of efficiency in education provision while the output of the public sector economics is used in determining the level of state intervention in the financing of higher education.